Masalah Pengadaan Tanah Untuk Proyek Strategis Nasional (PSN) - Roni Septian (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The National Strategic Project or better known as the PSN is a policy program that was born during the reign of President Joko Widodo. This program is highly prioritized because it is claimed to be able to help improve welfare and equitable development in various regions in Indonesia. The problem raised in this case is how the problem of land acquisition for the National Strategic Project (PSN). This research is normative legal research with statutory and conceptual approaches. The results of the study show that state facilities and instruments (law, state budget, incentives, bureaucrats and even the armed forces) are deployed to facilitate and protect SSA exploitation in Indonesia by entrepreneurs (PSN, KEK, FE, forests, plantations, mines). Meanwhile, tens of millions of farmers, fishermen, indigenous peoples and women are deliberately allowed to live in agrarian conflicts and poverty so as not to disturb SSA monopoly and exploitation by entrepreneurs.